Aryl Sulfonates as Initiators for Extreme Ultraviolet Lithography: Applications in Epoxy‐Based Hybrid Materials. Issue 5 (6th March 2018) - Torti, Edoardo; Protti, Stefano; Bollanti, Sarah; Flora, Francesco; Torre, Amalia; Brusatin, Giovanna; Gerardino, Annamaria; Businaro, Luca; Fagnoni, Maurizio; Della Giustina, Gioia; Mezi, Luca
Abstract: Two perfluoroaryl sulfonates were tested as initiators for the extreme ultraviolet (EUV)‐promoted polymerization of silica‐based hybrid organic‐inorganic films containing epoxy moieties. One of the sulfonates was able to strongly improve the polymerization efficiency in the tested materials and behaved much better than the commercial photoacid generator diphenylsulfonium (4‐phenylthiophenyl)diphenylsulfonium triflate. Furthermore, lithographic patterns with sub‐micrometric resolutions were achieved by irradiating resists containing the selected sulfonate (1 % molar concentration) at very low EUV doses (about 10 mJ cm −2 ). The proposed combination of specifically designed perfluoroaryl sulfonates and hybrid organic‐inorganic materials is a starting point to develop high‐performance and cost‐effective EUV‐sensitive resists for the microelectronic industry. Abstract : One for all and all for one…pattern : Perfluoroaryl sulfonates were tested as initiators for extreme ultraviolet (EUV) induced polymerization (λ=10–15 nm) on a hybrid organic–inorganic material. This combination gave very good results and sub‐micrometric structures were successfully achieved testing the developed systems in EUV patterning experiments, even at very low EUV doses.